Studying the Effect of Installing New Three Phase Separator on the Stabilization of Degassing Station - Al-Ali, Hussein (Journal of Petroleum Research and Studies, 2022)
The current work, studied the effect of replacing the existing two phase separator by three phase vessel on the off- specification quality for the produced oil. The true vapor pressure is set as the main criteria for the quality of product for an existing plant by using Aspen Hysys V9. To guarantee the process simulation is represent the real plant under operations, a comparative study was conducted between the simulation results and the plant data where it was a closely match with actual data to indicate that the simulation is a powerful tool, and it can be used for predicting the actual results. The existing plant operates with base sediment and water ratio no more than 15% while the studies expect to increase this ratio to 60% in future, for that this work is carried out by using Aspen Hysys V9.0 software to study the manipulating of different operating parameters such as dry oil flow rate, base sediments and water ratio, inlet temperature and the pressure of three phase vessel on the quality of product in term of TVP off-specification. By changing the different operating conditions, it has been found that the value of the true vapor pressure for the produced crude oil is less than 14 Psia/ 96.53 kPa. The obtained results conclude that the replacing of two phase separator by three phase vessel has no significant impacts on the true vapor pressure for the produced crude oil. The operating pressure for the three phase separator is revised and calculated where it is increased from 1176.8 kPa to 1330 kPa.